2020
DOI: 10.1093/ajcn/nqaa097
|View full text |Cite
|
Sign up to set email alerts
|

Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) authorization of discount variety stores: leveraging the private sector to modestly increase availability of healthy foods

Abstract: Background Many lower-income communities in the United States lack a full-line grocery store. There is evidence that the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) increases the availability of healthy foods in stores. One national discount variety store chain (DVS) that is often located in low-income neighborhoods became an authorized WIC vendor in 8 pilot stores. Objectives The objective o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The similarity of the association between redemption and failure to recertify across race/ ethnicity-language preference strata in the present study suggests that differences in redemption (non-Hispanic Black participants redeeming a smaller percent of WIC food benefits, Spanish-speaking Hispanic participants redeeming a higher percent of WIC food benefits) may contribute to race/ethnicity patterns in participation (14) . Further research is needed to understand factors contributing to observed differences in the distribution of redemption by race/ethnicity-language preference (22)(23)(24) , which may include availability of culturally appropriate substitutions within the WIC food packages (21,25) and structural barriers to WIC benefit redemption including access to WIC-participating vendors with desired WIC foods (26)(27)(28)(29) , and whether individual-and vendor-level interventions to increase redemption can reduce disparities in WIC retention.…”
Section: Discussionmentioning
confidence: 99%
“…The similarity of the association between redemption and failure to recertify across race/ ethnicity-language preference strata in the present study suggests that differences in redemption (non-Hispanic Black participants redeeming a smaller percent of WIC food benefits, Spanish-speaking Hispanic participants redeeming a higher percent of WIC food benefits) may contribute to race/ethnicity patterns in participation (14) . Further research is needed to understand factors contributing to observed differences in the distribution of redemption by race/ethnicity-language preference (22)(23)(24) , which may include availability of culturally appropriate substitutions within the WIC food packages (21,25) and structural barriers to WIC benefit redemption including access to WIC-participating vendors with desired WIC foods (26)(27)(28)(29) , and whether individual-and vendor-level interventions to increase redemption can reduce disparities in WIC retention.…”
Section: Discussionmentioning
confidence: 99%
“…Research has found that becoming a vendor led to an increases in both sales of healthy, WIC-eligible foods and in average weekly dollar sales, in comparison to similar stores that were not authorized as a WIC vendor [45]. Discount variety retailers provide an opportunity to provide healthy foods and beverages to low-income rural areas and urban food deserts [45,46]. These small-format stores sell an array of food, household, and other miscellaneous products at reduced prices.…”
Section: Discussionmentioning
confidence: 99%
“…Services provided (e.g., fast food versus “dining experience”) can also indicate a source’s targeted customer base (e.g., income/class, available time, cooking abilities/preferences). Products sold might also reflect a source’s priorities to generate additional revenue streams, such as stores that participate in federal assistance nutrition programs [ 52 ] to expand their customer base, as well as how much local demand is valued over operational convenience (e.g., product variation versus the same products at all locations) [ 53 ].…”
Section: Retail Food Environmentmentioning
confidence: 99%